EFFECT OF COMBINATION INORGANIC FERTILIZER WITH RICE WASHING WATER ON THE NUTRITIONAL CONTENT OF Spirulina sp. - Faustine Elvina Nuryadin, Devi; Ayi Meata, Bhatara; Nurazizatul Hasanah, Afifah; Afina Radityani, Fitri; Putra Suryono, Jundi; Dharmayanti, Wina; Basyair, Bunyamin; Udin, Ato (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2023)
Fertilizers commonly used in Spirulina sp. are walne, zarrouk, or guillard. However, the use of these fertilizers has several constraints, including the relatively expensive price, and requires quite a lot of nutrient solution composition in its manufacture. This problem is the reason for the search for alternative fertilizers for Spirulina sp. This study intends to provide information regarding the use of a combination of inorganic fertilizers from urea, plant catalyst, and GA with rice washing water as an alternative fertilizer which has a high nutritional content and can be used for Spirulina sp. it is followed by optical detachment analysis, water quality analysis, yield analysis, proximate analysis. The results of the study showed that the combination of inorganic fertilizers with rice washing water had a positive effect on the value of optical density with the fifth day of harvesting culture and proximate analysis of Spirulina sp. with the best treatment at P2 (1% inorganic fertilizer and 3 mL/L rice washing water) with culture water quality values in optimum conditions at a temperature of 29°C, pH 8 and salinity 19 ppt with an average yield of wet biomass, protein, fat, water, ash, and carbohydrates respectively 3.27 ±0.65, 5.42%, 1.62%, 88.54%, 3.22%, and 1.20%.